If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -1y = y + 2 Reorder the terms: 18 + -1y = 2 + y Solving 18 + -1y = 2 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 18 + -1y + -1y = 2 + y + -1y Combine like terms: -1y + -1y = -2y 18 + -2y = 2 + y + -1y Combine like terms: y + -1y = 0 18 + -2y = 2 + 0 18 + -2y = 2 Add '-18' to each side of the equation. 18 + -18 + -2y = 2 + -18 Combine like terms: 18 + -18 = 0 0 + -2y = 2 + -18 -2y = 2 + -18 Combine like terms: 2 + -18 = -16 -2y = -16 Divide each side by '-2'. y = 8 Simplifying y = 8
| 25n^2+64=0 | | 3x-(2x+5)=8x+(-2x+5) | | -3=x/4 | | -5x+6.9=-33.1 | | 1/4(9y-2)+1/8(6y+5) | | 3(6x-2)=9(2x-4) | | -5x^3+20xz^2=0 | | 3(2c-1)=4(c+5) | | 3/X+2/X+1/X=3/4 | | 8/3p-9-5/p-3=4 | | 8=12+5x | | k/9-3=11 | | 2b+3+3b=6-2b | | -2/9n=4/5 | | 2/5x=1/3 | | 100a^2-6=3 | | b-8=19 | | 2/5x=3/5 | | 2+x=3423423423 | | 3b+2=6b*3 | | 0=8n | | 98/7-9=5 | | -29.8r=59.6 | | 3x(5x+2)= | | f-4-3=-2 | | =3(2x-30) | | f-4-3=2 | | (M+5)+1.5=2 | | .44*7=x | | 15x+29(x-2)=294 | | o=v+1 | | 6x-24=-2x+32 |